KUALITAS DAMAR POHON POOTI (HOPEA GREGARIA) BERDASARKAN UJI VISUAL, BILANGAN ASAM, DAN KADAR ABU: Quality of Pooti Dammar Resin (Hopea gregaria) Based on Visual Test, Acid Number, and Ash Content - Zakiah Uslinawaty; Nurhayati Hadjar; Niken Pujirahayu; Nurmaningsih Hamzah; Abigael Kabe; Anggi Nurhafidzah (PERENNIAL, 2021)
Pooti (Hopea gregaria) is an endemic plant in Southeast Sulawesi that produces resin. But until now it has not been used because information about the quality of pooti resin has never been available. Therefore, this study aims to test the quality of pooti resin based on visual, acid number and ash content test. Pooti sap taken is on a tree with a diameter of 30 cm and a visual test is carried out based on SNI 2900-1-2012 and SNI 2900.2: 2013 for laboratory tests. The result is pooti resin with a clear yellowish color with a chunk size> 3x3 cm2, based on SNI 2900-1-2012 classified as Quality Class A. While the ash content value is 0.7% and the acid number is 29. This value indicates the ash content and acid number based on Laboratory tests are classified as quality class II based on SNI 2900.2: 2013.